The acceptability of a therapist-assisted Internet-delivered cognitive behaviour therapy program for the treatment of anxiety disorders in adolescents: a qualitative study - Smart, K; Smith, L; Harvey, K; Waite, P (Springer, 2021)
Introduction: Computerized treatments have been shown to be effective in young people with anxiety disorders. However, there has been limited investigation into the experiences of adolescents in undertaking this treatment. This qualitative study explored adolescents’ experiences of being treated for an anxiety disorder, using an online intervention with therapist support, as part of a randomised controlled trial.